2010
DOI: 10.1073/pnas.0909086107
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is a substrate of SYK tyrosine kinase in B-lineage leukemia/lymphoma cells exposed to oxidative stress

Abstract: We provide unprecedented genetic and biochemical evidence that the antiapoptotic transcription factor STAT3 serves as a substrate for SYK tyrosine kinase both in vitro and in vivo. Induction of SYK in an ecdysone-inducible mammalian expression system results in STAT3 activation, as documented by tyrosine phosphorylation and nuclear translocation of STAT3, as well as amplified expression of several STAT3 target genes. STAT3 activation after oxidative stress (OS) is strongly diminished in DT40 chicken B-lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(140 citation statements)
references
References 57 publications
12
127
0
1
Order By: Relevance
“…It has been reported that STAT3 is activated by oxidative stress. 45 To evaluate the oxidative stress induced by mutant IDH1, we measured ROS accumulation in mutant IDH-expressing clones, but were unable to detect any significant increase of ROS. It is possible that 2HG may modulate the oxidative state of specific metabolites, which were not detectable under the conditions we used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that STAT3 is activated by oxidative stress. 45 To evaluate the oxidative stress induced by mutant IDH1, we measured ROS accumulation in mutant IDH-expressing clones, but were unable to detect any significant increase of ROS. It is possible that 2HG may modulate the oxidative state of specific metabolites, which were not detectable under the conditions we used.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required to examine specific signaling pathways that are affected by increased mitochondrial superoxide. It would be predicted that redox-sensitive signaling cascades such as NF-κB [17], AP-1 [15], or JAK/STAT [18] may be affected and, as such, may in part in explaining the pseudo-activated state and microarray results observed in this study. Furthermore, the role of posttranslational modifications on proteins such as the hypoxia-inducible factor could also provide valuable information on how ROS regulate cellular signaling [62].…”
Section: Discussionmentioning
confidence: 77%
“…More recently it has been shown that cells possess the ability to exploit ROS for signaling and functional purposes. For example, many transcription factor pathways are sensitive to oxidative stress and as such are able to help cells adapt to large deviations in redox status [15][16][17][18]. Moreover, ROS are essential in the development of certain organ systems and even whole organisms [19,20].…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact SH2 and PH domains are required for a full recovery of Btk-mediated oxidative stress-induced intracellular calcium mobilization, although mutation of the SH2 (Arg307 to Ala) or PH (Arg28 to Cys) domain did not affect the oxidative stress-induced activation of Btk. Interestingly, Syk SH2 domains play different roles on substrate selectivity as Syk SH2 domains has no effect on oxidative stressinduced phosphorylation of STAT3 [30] . The overall results demonstrate that functional SH2 and PH domains are required for Btk to form a complex with PLCγ2 through BLNK in order to position the Btk, PLCγ2, and phosphatidylinositol 4,5-bisphosphate in close proximity for efficient activation of PLCγ2 and to maximize its catalytic efficiency for IP3 production [29] .…”
mentioning
confidence: 99%